SOCIAL MEDIA ON CAMPUS: STUDI PERAN MEDIA SOSIAL SEBAGAI MEDIA PENYEBARAN INFORMASI AKADEMIK PADA MAHASISWA DI PROGRAM STUDI ILMU KOMUNIKASI FISIP UNSRI - Meilinda, Nurly (The Journal of Society and Media, 2018)
The development of communication technology is a necessity and inevitable. This fenomena have changed the way people interact. One of the groups that affected by the development of communication technology is the college students. This study aims to determine the role of social media as a medium of dissemination about academic information among students in the Communication Program in Sriwijaya University. This study uses qualitative methods, and data collection methods through in-depth interviews with 8 students. The study found that informants spend 5-10 hours a day accessing the internet, and most of the time it is used to access social media. The application used in this case is Line, and Whatsapp. Social media is currently the main media used by students to seek academical information, rather than seeking information directly to the dean office, rectorate, or campus official website